An Empirical Study on Challenges and Strategies to Employability for Graduates - Indra Devi Kandasamy, Rozainun Abdul Aziz, (Opción, 2019)
This paper aims to examine the challenges and strategies for graduate employability. A bilinear cost function is offered to formulate strategies in addressing challenges, that expresses outcomes and benefits as a result. This paper offers strategies that can be used as options to overcoming challenges to enhance employability for the graduates. A proposed framework and checklist are provided that includes advanced training, probation, professional qualification and certifications, endorsed-employer skills, among others. It is hoped that readers will consider the results of this study as strategies to resolve the employability challenges.